2013
DOI: 10.1007/s11302-013-9392-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds with P2X7 receptor-modulating properties

Abstract: The adenosine 5′-triphosphate (ATP)-gated P2X7 receptor is a membrane-bound, non-selective cation channel, expressed in a variety of cell types. The P2X7 senses high extracellular ATP concentrations and seems to be implicated in a wide range of cellular functions as well as pathophysiological processes, including immune responses and inflammation, release of gliotransmitters and cytokines, cancer cell growth or development of neurodegenerative diseases. In the present study, we identified natural compounds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The competitive antagonist A438079, which is known to inhibit pore formation, decreased YoPro-1 uptake in all PDAC cell lines tested. This agrees with the P2X7 receptor-pore inhibitor characteristic of A438079 also described in pancreatic stellate cells, HEK293 cells and A375 human melanoma cells [ 17 , 50 , 51 ]. Although the pore formation is modest with high concentrations of ATP, as detected by the standard YoPro-1 analysis over 60 min, during long-term incubation with ATP, PDAC cells died with signatures of necrosis (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The competitive antagonist A438079, which is known to inhibit pore formation, decreased YoPro-1 uptake in all PDAC cell lines tested. This agrees with the P2X7 receptor-pore inhibitor characteristic of A438079 also described in pancreatic stellate cells, HEK293 cells and A375 human melanoma cells [ 17 , 50 , 51 ]. Although the pore formation is modest with high concentrations of ATP, as detected by the standard YoPro-1 analysis over 60 min, during long-term incubation with ATP, PDAC cells died with signatures of necrosis (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we observed that the modulator TFP had a potentiating effect on Yo-Pro-1 uptake exclusively on the murine receptor but not on the humanized P2X7R. Species-specific effects of positive and negative modulators have repeatedly been described for P2X7R orthologs [8, 10, 57, 58]. These findings suggest that our humanized mouse model is well-suited to discriminate properties of mouse and human P2X7R orthologs in an in vivo context and thereby opens new possibilities for the screening and evaluation of new P2X7R agonists and antagonists.…”
Section: Discussionmentioning
confidence: 89%
“…P2X 7 R reported being constitutively expressed on MΦ surfaces and also reported to be associated with signaling cascades of inflammation, apoptosis and subsequent intracellular pathogen control (Miller et al, 2011). Additively, intracellular anti-leishmanial attributes of Spergulin-A demonstrating the involvement of the purinergic receptor P2X 7 also hypothesized on the reports of compounds screened towards the purinergic receptor amendments that about one-third of the structurally diversified compounds are being natural products with a proven affinity towards these purinergic receptors (Fischer et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Screening compounds toward purinergic receptor modifications have identified structurally diversified compounds over two thousand and almost one-third of them are being natural products having an affinity towards these receptors. As for example teniposide, a semisynthetic podophyllotoxin derivative can inhibit P2X 7 R, whereas, agelasine and garcinolic acid (Fischer et al, 2014), potentially activate the same. In recent years efforts are made towards the identification of compounds that can modulate P2X receptors aiming towards novel chemotherapeutic measurements towards diseases associated with inflammation (Bartlett et al, 2014;Stokes et al, 2017).…”
mentioning
confidence: 99%